2017
DOI: 10.1002/qua.25490
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic activation of nitrobenzene on PVP passivated silver cluster: A DFT investigation

Abstract: Poly(N‐vinyl‐2‐pyrrolidone) (PVP) has been used extensively to stabilize the surface of noble metal nanoparticles against aggregation and also to produce anisotropic nanostructures. Naturally, it is very important to understand the effect of such surface stabilization by PVP on the catalytic activity of these nanoparticles. This communication investigates through DFT calculations the electronic properties of PVP stabilized 13‐atom Ag cluster for catalytic activation of nitrobenzene (NB). These computations sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…6 Modification of transition metal nanocatalysts with functionalizing agents such as surfactants 7,8 or polymers 9 has helped to improve stability against aggregation but such modification often deteriorates the catalytic properties via changes in the electronic structure of metal nanocatalysts. 10 The alternative way proposed to overcome the aggregation and deterioration of catalytic property is the implanting or anchoring of nanocatalysts on inert low density solid supports. The solid supports help to maintain the size, shape, morphology of nanocatalysts and also limit the leaching of metal ions favorable for achieving durable and enhanced catalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…6 Modification of transition metal nanocatalysts with functionalizing agents such as surfactants 7,8 or polymers 9 has helped to improve stability against aggregation but such modification often deteriorates the catalytic properties via changes in the electronic structure of metal nanocatalysts. 10 The alternative way proposed to overcome the aggregation and deterioration of catalytic property is the implanting or anchoring of nanocatalysts on inert low density solid supports. The solid supports help to maintain the size, shape, morphology of nanocatalysts and also limit the leaching of metal ions favorable for achieving durable and enhanced catalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, limited studies have taken up the issue of effect of IL stabilization on the catalytic properties of these particles. This becomes topical in view of the fact that a few recent experimental as well as theoretical investigations have shown that many macromolecules (other than ILs) stabilizing nanoparticles also affect their electronic structures and thereby their catalytic activity [4,5,6]. Imidazolium based ionic liquids have highly structural organization at nanoscale level and in the condensed phase [7], containing supramolecular networks held together by hydrogen bonds and πÀπ stacking between imidazolium rings [8,9] Synthesis, interaction and organization of NPs in ILs have been explained deeply by He et.al [10].…”
Section: Introductionmentioning
confidence: 99%
“…PVP has not only been shown to stabilize NCs in solution but also has been shown to actively take part in the catalytic process by altering the electronic distribution and hence enhancing the catalytic activity of the NCs. [41,49,50] The concentration and length of PVP and stabilizers in general also has a significant effect on the size and shape of nanoparticles synthesized. The structures and dynamics of polymer dispersed NCs are poorly understood and NC catalyzed reaction modeling is usually carried out on pristine clusters.…”
Section: Introductionmentioning
confidence: 99%